Large-scale structures in the Earth’s interior: Top-down hemispherical dynamics constrained by geochemical and geophysical approaches - Iwamori, Hikaru; Yoshida, Masaki; Nakamura, Hitomi (Frontiers in Earth Science, 2022)
Geochemical and geophysical observations for large-scale structures in the Earth’s interior, particularly horizontal variations of long wavelengths such as degree-1 and degree-2 structures, are reviewed with special attention to the cause of hemispherical mantle structure. Seismic velocity, electrical conductivity, and basalt geochemistry are used for mapping the large-scale structures to discuss thermal and compositional heterogeneities and their relations to dynamics of the Earth’s interior. Seismic velocity structure is the major source of information on the Earth’s interior and provides the best spatial resolution, while electrical conductivity is sensitive to water/hydrogen contents. The composition of young basalts reflects the mantle composition, and the formation age of large-scale structures can be inferred based on the radiogenic isotopes. Thus, the different research disciplines and methods complement each other and can be combined to more concretely constrain the structures and their origins. This paper aims to integrate observations from these different approaches to obtain a better understanding of geodynamics. Together with numerical modeling results of convection in the mantle and the core, “top-down hemispherical dynamics” model of the crust-mantle-core system is examined. The results suggest that a top-down link between the supercontinents, mantle geochemical hemisphere, and inner core seismic velocity hemisphere played an essential role in formation of the large-scale structures and dynamics of the Earth’s interior.